Trophic ecology of large herbivores in a reassembling African ecosystem. (31st December 2018) - Pansu, Johan; Guyton, Jennifer A.; Potter, Arjun B.; Atkins, Justine L.; Daskin, Joshua H.; Wursten, Bart; Kartzinel, Tyler R.; Pringle, Robert M.
Abstract: Megafauna assemblages have declined or disappeared throughout much of the world, and many efforts are underway to restore them. Understanding the trophic ecology of such reassembling systems is necessary for predicting recovery dynamics, guiding management, and testing general theory. Yet, there are few studies of recovering large‐mammal communities, and fewer still that have characterized food‐web structure with high taxonomic resolution. In Gorongosa National Park, large herbivores have rebounded from near‐extirpation following the Mozambican Civil War (1977–1992). However, contemporary community structure differs radically from the prewar baseline: medium‐sized ungulates now outnumber larger bodied species, and several apex carnivores remain locally extinct. We used DNA metabarcoding to quantify diet composition of Gorongosa's 14 most abundant large‐mammal populations. We tested five hypotheses: (i) the most abundant populations exhibit greatest individual‐level dietary variability; (ii) these populations also have the greatest total niche width (dietary diversity); (iii) interspecific niche overlap is high, with the diets of less‐abundant species nested within those of more‐abundant species; (iv) partitioning of forage species is stronger in more structurally heterogeneous habitats; and (v) selectivity for plant taxa converges within guilds and digestive types, but diverges across them. Abundant (and narrow‐mouthed) populations exhibited higher among‐individual dietary variation, but not necessarily the greatest dietary diversity. Interspecific dietary overlap was high, especially among grazers and in structurally homogenous habitat, whereas niche separation was more pronounced among browsers and in heterogeneous habitat. Patterns of selectivity were similar for ruminants—grazers and browsers alike—but differed between ruminants and non‐ruminants. Synthesis . The structure of this recovering food web was consistent with several hypotheses predicated on competition, habitat complexity, and herbivore traits, but it differed from patterns observed in more intact assemblages. We propose that intraspecific competition in the fastest‐recovering populations has promoted individual variation and a more nested food web, wherein rare species use subsets of foods eaten by abundant species, and that this scenario is reinforced by weak predation pressure. Future work should test these conjectures and analyse how the taxonomic dietary niche axis studied here interacts with other mechanisms of diet partitioning to affect community reassembly following wildlife declines. Abstract : The structure of this recovering food web was consistent with several hypotheses predicated on competition, habitat complexity, and herbivore traits, but it differed from patterns observed in more intact assemblages. We propose that competition and the extirpation of top predators have promoted individual variation, inter‐specific niche overlap and a more nested food web wherein rare species use subsets of foods eaten by abundant species.